ANALYSIS OF THE GOVERNMENT'S ROLE IN FACILITATING THE BATTERY-BASED ELECTRIC MOTOR VEHICLE INDUSTRY FOR ROAD TRANSPORTATION - Purnomo, Mico Ariel Wahyu (Journal Education and Government Wiyata, 2023)
Study discusses the government's efforts to overcome the problem of climate change that is occurring in Indonesia by utilizing electric vehicles. It is felt that climate change is a concern for all countries in the world. This is caused by human effectiveness factors or naturally changing climate. The study method used in this study is to carry out a SWOT analysis which aims to formulate a strategy to increase the market for the use of electric vehicles so that it can overcome the problem of climate change in Indonesia. The data collection technique used in this study is literature study and literature from previous studies . The results of the study explain that the government has made various efforts to reduce carbon emissions and increase the use of electric vehicles by issuing policies in the form of presidential regulations and presidential instructions. And based on the results of the SWOT analysis, the use of electric vehicles has the potential to replace conventional vehicles in overcoming climate change in Indonesia .